PUBLIC BATHS & GENDER RECONSTRUCTION IN THE MANGKUNEGARAN REGION OF SOLO - Saffana, Fiera; Marwoto, Irmawati (UI Scholars Hub, 2025)
The division of gender roles in space is already evident from the layout of traditional Javanese buildings, which reflects a patriarchal culture where men are at a higher level than women. These gender boundaries and norms are also reflected in the spatial form of public bath in Solo. This research uses the archaeological method by Deetz which consists of data collection, data processing, and data interpretation. Explaining by presenting facts based on data obtained in the field, then data processing is carried out by involving analysis of the field data that has been collected. The last stage is the interpretation of data on Mangkunegaran’s Solo public bath. The spatial layout is interpreted by considering the spatial and gender context. This research aims to understand how the understanding of the reconstruction of gender aspects is reflected in the form of a spatial system in Solo public bath built by Mangkunegaran. The results of this study show that gender, although an abstract social construction, has a real manifestation in the spatial layout of the building that can be observed through various aspects. The space designated for men contains primary and masculine values and has an open character, while the space for women contains secondary, feminine, and closed values. This research also found that the spatial arrangement reflects not only social status but also gender hierarchy.